Surgical Site Infection Rate after Hemilaminectomy and Laminectomy in Dogs without Perioperative Antibiotic Therapy - Dyall, Barbara A.R.; Schmökel, Hugo G. (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Objective The aim of this study was to retrospectively review the surgical site infection (SSI) rate in dogs undergoing laminectomies without perioperative antibiotics, and compare those data with the expected infection rate for clean surgical wounds in dogs undergoing similar procedures.Methods This was a retrospective single-centre study composed of dogs that underwent hemilaminectomies or laminectomies for thoracolumbar disc herniation or lumbosacral disease during a 2-year period (during 2015 and 2016). All incisional complications within 30 days were recorded and divided into superficial, deep or organ/space infections. Those dogs that received perioperative or postoperative antibiotics due to non-related comorbidities and those with incomplete medical records during the study period were excluded.Results Of 221 consecutive hemilaminectomy and laminectomy procedures, 154 were included in this research study. One superficial wound infection was recorded and treated with antimicrobials. Overall, the SSI rate was 0.6%, while the expected SSI rate in clean operative wounds in dogs and cats is 2.0 to 4.8%. The SSI rate in human spinal surgery is 0.7 to 4.3%.Clinical Significance Considering the low incidence of SSI in our study group, the routine use of perioperative antibiotic prophylaxis in dogs undergoing laminectomy procedures should be reconsidered to help address the global problem of bacterial resistance.
Keywords: infection rate; laminectomy; perioperative antibiotic therapy; surgical site infection; hemilaminectomy